Re-examining the Expiration Effects of Index Futures: Evidence from India - Singh, Gurmeet; Shaik, Muneer (International Journal of Economics and Financial Issues, 2020)
This study investigates the expiration effects of stock index futures before and after the introduction Bank Nifty weekly options from April 2013 to June 2019. To check for the expiration effects, the volume and mean returns for expiration groups is compared with non-expiration groups or comparison groups. We had a total of 74 expiration dates; 37 expiration dates are before the introduction Bank Nifty weekly option and 37 are after the introduction Bank Nifty weekly options. The current study used t-test, pooled t- test, and Wilcoxon rank sum test to investigate if the mean return and volume for expiration were significantly different from the comparison group. We also check day of the week and if there is significant difference in nifty futures returns based on different expiration dates using Kruskal-Wallis test. The finding of the study found trading volume for the expiration groups is significantly different from the comparison. There was evidence of high return, low volatility and decrease in volume after the introduction of Bank Nifty weekly option. Keywords: Stock Market, Expiration Month, Expiration Week, Expiration Day JEL Classifications: G12, G 14 DOI: https://doi.org/10.32479/ijefi.9429